Monitoring redox stress in human airway epithelial cells exposed to woodsmoke at an air–liquid interface - Aiman Abzhanova; Jon Berntsen; Edward R. Pennington; Lisa Dailey; Syed Masood; Ingrid George; Nina Warren; Joseph Martin; Michael D. Hays; Andrew J. Ghio; Jason P. Weinstein; Yong Ho Kim; et al. (Particle and Fibre Toxicology, 2024)
Abstract Wildland fires contribute significantly to the ambient air pollution burden worldwide, causing a range of adverse health effects in exposed populations. The toxicity of woodsmoke, a complex mixture of gases, volatile organic compounds, and particulate matter, is commonly studied in vitro using isolated exposures of conventionally cultured lung cells to either resuspended particulate matter or organic solvent extracts of smoke, leading to incomplete toxicity evaluations. This study aimed to improve our understanding of the effects of woodsmoke inhalation by building an advanced in vitro exposure system that emulates human exposure of the airway epithelium. We report the development and characterization of an innovative system that permits live-cell monitoring of the intracellular redox status of differentiated primary human bronchial epithelial cells cultured at an air–liquid interface (pHBEC-ALI) as they are exposed to unfractionated woodsmoke generated in a tube furnace in real time. pHBEC-ALI exposed to freshly generated woodsmoke showed oxidative changes that were dose-dependent and reversible, and not attributable to carbon monoxide exposure. These findings show the utility of this novel system for studying the molecular initiating events underlying woodsmoke-induced toxicity in a physiologically relevant in vitro model, and its potential to provide biological plausibility for risk assessment and public health measures.